Corneal Classics: The Most-Cited Article in the 36-Year History of Cornea. Issue 3 (13th March 2021) - Perry, Henry D.
Abstract : Purpose: To describe the most cited article in the 36 year history of Cornea. Methods: All articles from Cornea in the past 36 years were reviewed to find the the article with the greatest number of citations. Results: Descemet-Stripping Automated Endothelial Keratoplasty by Mark S. Gorovoy, MD, Cornea 2006;25:886–889 was found to have the greatest number of citations. Conclusion: This study led to the single greatest change of cornea transplant going from Penetrating Keratoplasty to Descemet Stripping Automated Endothelial Keratoplasty.